Assessment of riverine load of contaminants to european seas under policy implementation scenarios: An example with 3 pilot substances. (21st November 2013) - Marinov, Dimitar; Pistocchi, Alberto; Trombetti, Marco; Bidoglio, Giovanni
Abstract An evaluation of conventional emission scenarios is carried out targeting a possible impact of European Union (EU) policies on riverine loads to the European seas for 3 pilot pollutants: lindane, trifluralin, and perfluorooctane sulfonate (PFOS). The policy scenarios are investigated to the time horizon of year 2020 starting from chemical‐specific reference conditions and considering different types of regulatory measures including business as usual (BAU), current trend (CT), partial implementation (PI), or complete ban (PI ban) of emissions. The scenario analyses show that the model‐estimated lindane load of 745 t to European seas in 1995, based on the official emission data, would be reduced by 98.3% to approximately 12.5 t in 2005 (BAU scenario), 10 years after the start of the EU regulation of this chemical. The CT and PI ban scenarios indicate a reduction of sea loads of lindane in 2020 by 74% and 95%, respectively, when compared to the BAU estimate. For trifluralin, an annual load of approximately 61.7 t is estimated for the baseline year 2003 (BAU scenario), although the applied conservative assumptions related to pesticide use data availability in Europe. Under the PI (ban) scenario, assuming only small residual emissions of trifluralin, we estimate a sea loading of approximately 0.07 t/y. For PFOS, the total sea load from all European countries is estimated at approximately 5.8 t/y referred to 2007 (BAU scenario). Reducing the total load of PFOS below 1 t/y requires emissions to be reduced by 84%. The analysis of conventional scenarios or scenario typologies for emissions of contaminants using simple spatially explicit GIS‐based models is suggested as a viable, affordable exercise that may support the assessment of implementation of policies and the identification or negotiation of emission reduction targets. Integr Environ Assess Manag 2013;X:000–000. © 2013 SETAC Integr Environ Assess Manag 2014;10:48–59. © 2013 SETAC